(untitled) (Eureka Journal of Education & Learning Technologies, 2026)
The article examines the problem of developing creative thinking in preschool children through musical activities. Special attention is paid to musical improvisation as an effective method for stimulating creativity, imagination, and emotional responsiveness in young children. The psychological and pedagogical features of using improvisational activities in the educational process of preschool institutions are revealed, as well as their impact on the formation of independence, initiative, and imaginative thinking. The importance of creating an emotionally supportive environment that promotes a child’s free self-expression through music is substantiated. The article presents methodological approaches to organizing musical improvisation activities and highlights their role in developing the creative potential of preschool children. It concludes that musical improvisation is a highly effective means of fostering creative thinking within the preschool education system.